Peran Teknologi Komunikasi dalam mendukung Proses Pembelajaran di Era Pandemi Covid-19 - Ely Suwaibatul Aslamiyah (Al-Maquro' : Jurnal Komunikasi dan Penyiaran Islam, 2020)
The existence of the coronavirus / COVID-19 epidemic that hit the whole world, has, directly and indirectly, changed the way of human life. Things that had never been done now inevitably have to be accustomed to. This applies also to the world of education. The learning process inevitably has to adapt to be able to continue. Communication technology is the backbone of implementing the learning process in the co-19 pandemic era. In this research, it is proven that information technology has an important role in supporting the learning process in the Covid-19 pandemic era. Online learning is the most ideal option in implementing the learning process with the coronavirus threat.